Combination of ethanolic extract on total flavonoid Centella asiatica L. leaves and Imperata cylindrica L. roots with UV-VIS spectrophotometric method - Anita Puspa Widiyana; Sri Herlina; Didi Nurhadi Illian (Universitas Islam Indonesia, 2022)
Background: Flavonoids are widely employed as phytomedicines and as secondary metabolites generated by plants, where they serve key roles in plant physiology. Antioxidant, anti-inflammatory, anticancer, antibacterial, antifungal, and antiviral activities are only a few of the potential biological effects of flavonoids. The discovery of medicinal plants containing flavonoid chemicals is potential as a supportive and preventative treatment, notably for COVID-19 which has caused a pandemic in several countries, including Indonesia.Objective: This study aimed to determine the total flavonoid content in the ethanolic extracts of C. asiatica leaves and Imperata cylindrica roots to find the potential of flavonoid-rich plants as an alternative source of COVID-19 treatment.Methods: The ethanolic extracts from the combination of C. asiatica leaves and I. cylindrica roots (with five combination ratios) were tested for total flavonoid content using the UV-Vis Spectrophotometry method. The total flavonoid content of the extract combination was analyzed using a one-way ANOVA test.Results: The total flavonoid contents of the combination of C. asiatica leaf and I. cylindrica root extracts at a ratio of 1:1, 2:3, 3:2, 4:1, and 1:4 were 45.88 ± 0.08, 42.14 ± 0.08, 40.52 ± 0.08, 66.28 ± 0.08, and 40.88 ± 0.13 mg/g EQ, respectively. The homogeneity with Levene's test obtained a p-value of 0.303. The one-way ANOVA exhibited the p-value of F-test statistics < 0.001. Conclusion: The total flavonoid contents of ethanolic extracts from C. asiatica leaves and I. cylindrica roots are at a ratio of 4:1 > 1:1 > 2:3 > 1:4 > 3:2. The high total flavonoid content plays a role in increasing anti-inflammatory and immunomodulatory activities in COVID-19 patients.Keywords: Total flavonoid content, C. asiatica, I. cylindrica, UV-Vis Spectrophotometry, COVID-19